Penyuluhan Manfaat Khitanan Bagi Kesehatan Dan Khitanan Massal Dilaksanakan Di Akademi Kesehatan Kartini Batam - Derry Trisna Wahyuni S; Alif Rahman Habibi; Hardiyanti Hardiyanti; Hartati Hartati; Nurul Qomariah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The process of removing the skin covering the tip of the penis is known as circumcision. The law of circumcision for boys in Islam is mandatory. The goal is not only to obey religious orders, but also to prevent feces from sticking to the penis, making urination easier, and reducing the pleasure of intercourse. Apart from that, there are many benefits of circumcision after doing it, but there are still children who don't know what circumcision is and its benefits based on data analysis. The community will be given free circumcisions to carry out one of the Tridharma activities of higher education which is being carried out in Batam City. At this stage, the children were circumcised by doctors from Budi Kemuliaan Hospital, assisted by lecturers from the Kartina Batam Health Academy and lecturers from the Putra Jaya Health Analytical Academy, Batam. After the circumcision process, it is checked again after 3 days. Through the implementation of Community Service in 2024, the target of this activity is to provide education to the public to avoid various kinds of genital diseases, so that public health can be more guaranteed. Circumcision not only functions to clean vital human organs, but circumcision has many health benefits, including AIDS, penile cancer, prostate cancer and urinary tract infections.